Iranian EFL Learners` Use of Metadiscourse Markers in Argumentative Writing - Mostafa Rahimi Rad (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This paper is an attempt to investigate the EFL Iranian learners` use of metadiscourse markers in argumentative writing. The participants of the study are 40 students both male and female. To produce the relevant data, participants were given a pretest of writing ability to check their initial knowledge use of metadiscourse markers. Finally, a post test assessing their writing ability with metadiscourse markers was administered. Writing is a social activity and it is supposed as an important factor of literacy in society despite being mastered in English, students from different cultures and with different first languages seem to be different in developing writing texts.  Metadiscourse markers enable the writers to interact with the readers effectively. The findings revealed that both male and female writers employed more interactive markers than interactional markers due to the fact that both genders inserted transition markers frequently to guide readers through the texts. The findings indicated generally that instruction of metadiscourse markers significantly improves EFL learners’ writing ability of advanced students. The Teachers pay more attention to metadiscourse markers in making EFL curricula. Then they ask for the reinforcement of metadiscourse markers through instruction in EFL courses for the improvement of the learners' writing ability.